Sustainable and optimum generation mix possibilities for Malaysia power sector / Ahmad Amiruddin Mohammad Aris - Mohammad Aris, Ahmad Amiruddin (2013)
Malaysia generation mix has been long time dependence on a single fuel. This over-dependency is not a good option for long-term energy sustainability and security. This has led Malaysia to find other alternative resources to generate electricity. Some possible options are firstly using coal, however this leads to the dependency on imported coal and increase CO2 emission. Secondly by using Nuclear power plant, however the recent Fukushima incident and the public acceptance are the major consideration. Lastly using renewable energy (RE), however the resources are interruptible and expensive. This report proposes a study to determine optimal long-term generation mix for Malaysia using DP-based model at least cost.